Reed: 3d printed wearable device to manage anxiety through melodic mindfulness - Hapiz, Hana; Ahmad, Nooraziah; Ibrahim, Yuhanis; Abdul Latef, Azlin Sharina; Radzuan, Ainul Wahida; Mohd Zain, Mohd Zaimmudin (Universiti Teknologi MARA, Kedah, 2023)
Breathing is a powerful tool for managing anxiety. Reed, which is a two-inch stainless-steel device that looks like a harmonica. The purpose of this tool is to teach breath control to alleviate anxiety. While Reed may not eliminate the stresses of daily life, it can be used to lessen feelings of anxiety, calm the mind, and alleviate tension during particularly overwhelming moments. Reed aims tochoreograph users with anxiety to how to do breathe during the anxious episode. Deep breaths can help to activate the ventral vagal branch of the nervous system, which promotes feelings of calm and relaxation. This wearable harmonica emits slow melodic sound to sooth the wearer and also guide the right breathing techniques to calm the nerves. By stimulating the vagus nerve, which connects the brain to the body's organs, slow breathing can help to regulate heart rate, blood pressure, and other physiological responses to stress.